Cognitive Task Analysis Against the Low Implementation of Data-Based Instructional Design in Kindergarten Teachers' Differentiated Learning Practices - Ratna Juwita (JTP - Jurnal Teknologi Pendidikan, 2026)
The main objective of this study is to analyze the cognitive barriers that underlie the limited transformation of assessment data into proactive instructional design in the practice of Differentiated Instruction (DI) among Kindergarten teachers. The method used is descriptive qualitative with a Cognitive Task Analysis (CTA) approach to uncover expert decision-making processes that are often implicit. The research subjects involved 31 expert teachers from 31 districts/cities in Indonesia, with data collected through STAR essays, practice video recordings, and structured interviews. The analysis was carried out using the parameters of the DI 4:9:2 skill formula, which included the preparation, implementation, and evaluation phases. The results of the study revealed a significant phenomenon of "practice fragmentation"; Although 42% of kindergarten teachers routinely conduct pre-assessments, only 3% use them to determine learning objectives and materials. Teachers showed high dominance in reactive differentiation through the provision of additional support (90.32%) but very low dominance in proactive adaptation of instruction (26%). These findings suggest a cognitive barrier in "data translation" skills in the preparatory phase, where assessment is often only an administrative formality, rather than a pedagogical foundation. The main recommendation of this study is to reorient the teacher professional development program from merely a data-collection tool to one that strengthens skills in assessment-based instructional design. In addition, strengthening Learning Communities is highly recommended to facilitate the sharing of cognitive strategies and "rules of thumb" to bridge the gap between assessment data and adaptive learning planning.